Prediction of anastomotic leakage after anterior rectal resection - Cheng, Shubang (Pak J Med Sci, 2019)
OBJECTIVE: Anastomotic Leakage (AL) is one of the most common complications after resection of rectal cancer. Recognition of the incidence and risk factors related to AL is important. This study aimed develops a model that can predict anastomotic leakage after anterior rectal resection. METHODS: Data from 188 patients undergoing anterior resection of rectal cancer were collected for retrospective analysis. Patients were randomly divided in the development set and validation set at a 1:1 ratio. We first included age, sex, preoperative chemoradiotherapy, tumor size, degree of tumor differentiation, stage, TNM stage, lymph vascular invasion, distance, anastomotic method, diabetes, intraoperative time, intraoperative bleeding and smoking as candidates for variable selection with a LASSO method. A ROC curve was constructed with the validation set to assess the accuracy of the prediction model. RESULTS: AL occurred in 20 of 188 patients (10.6%). Preoperative chemoradiotherapy (p=0.04), medium degree of tumor differentiation (p=0.04), anastomotic method (p<0.01), intraoperative bleeding≥400ml (p<0.01), smoking (p<0.01), diabetes (p<0.01) were significantly related to AL. The area under the ROC curve of the prediction model is 0.952. CONCLUSIONS: This study developed a model that can predict anastomotic leakage after anterior rectal resection, which may aid the selection of preventive ileostomy and postoperative management.